Understanding of Crucial Factors for Improving the Energy Density of Lithium-Sulfur Pouch Cells - Leonet, Olatz; Doñoro, Álvaro; Fernández-Barquín, Ana; Kvasha, Andriy; Urdampilleta, Idoia; Blázquez, J. Alberto (Frontiers in Chemistry, 2022)
Rechargeable lithium−sulfur (Li−S) batteries are the most promising next-generation energy storage system owing to their high energy density and low cost. Despite the increasing number of publications on the Li-S technology, the number of studies on real prototype cells is rather low. Furthermore, novel concepts developed using small lab cells cannot simply be transferred to high-energy cell prototypes due to the fundamental differences. The electrolyte and lithium anode excess used in small lab cells is known to have a huge impact on the cycle life, capacity, and rate capability of the Li-S system. This work analyses the performance of pouch cell prototypes demonstrating the potential and hurdles of the technology. The impact of electrolyte variations and the sulfur cathode loading are studied. The energy density of Li-S pouch cell is improved up to 436 Wh kg−1 by a combination of different approaches related to cell manufacturing, sulfur cathode optimization, and electrolyte amount adjustment.